Adult Pyloric Stenosis Masquerading as Acute Renal Failure - Siow, Sze Li; Wong, C. M.; Sohail, Mushtaq (Malaysian Medical Association, 2009)
Gastric outlet obstruction and in particular, pyloric stenosis, is relatively common in developing countries. Acute clinical presentation is often the manifestation of biochemical and electrolyte changes. The presence of metabolic alkalosis in combination with acute renal failure should alarm us to the possibility of adult pyloric stenosis. We report a case of adult pyloric stenosis that presented as acute renal failure and discuss its pathophysiology.